2014
DOI: 10.1037/h0101800
|View full text |Cite
|
Sign up to set email alerts
|

The benefit of retrieval practice over elaborative restudy in primary school vocabulary learning.

Abstract: Link to publication General rightsCopyright and moral rights for the publications made accessible in the public portal are retained by the authors and/or other copyright owners and it is a condition of accessing publications that users recognise and abide by the legal requirements associated with these rights.• Users may download and print one copy of any publication from the public portal for the purpose of private study or research. • You may not further distribute the material or use it for any profit-makin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…This finding was also observed in preschoolers' memory for past events (Hudson, 1990;Hudson and Sheffield, 1998). However, other studies have observed no benefit of retrieval practice in young children (Poole and White, 1991;Ornstein et al, 2006;Goossens et al, 2014;Karpicke et al, 2014). For instance, preschoolers performed comparably on a cued-recall task when the experimenter provided the word for a cue (snow-white) vs. when children were asked to generate the word themselves (e.g., snow-_____; Carneiro et al, 2018).…”
Section: Introductionmentioning
confidence: 62%
See 3 more Smart Citations
“…This finding was also observed in preschoolers' memory for past events (Hudson, 1990;Hudson and Sheffield, 1998). However, other studies have observed no benefit of retrieval practice in young children (Poole and White, 1991;Ornstein et al, 2006;Goossens et al, 2014;Karpicke et al, 2014). For instance, preschoolers performed comparably on a cued-recall task when the experimenter provided the word for a cue (snow-white) vs. when children were asked to generate the word themselves (e.g., snow-_____; Carneiro et al, 2018).…”
Section: Introductionmentioning
confidence: 62%
“…Performance was only improved after substantial memory supports were provided (i.e., children filled out a partially completed concept map). However, too much scaffolding at test can also lead to null results: in one study, retrieval practice benefited a fill-in-the-blank vocabulary test but did not benefit performance on a multiple-choice test due to ceiling effects (Goossens et al, 2014). Why does retrieval practice fail to improve children's learning in these situations?…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This cognitive strategy has been extensively explored by experimental psychologists. Traditionally, this research has taken place in laboratory settings using diverse learning materials, such as word lists or pairs (Carpenter, 2009;Cranney et al, 2009;Halamish & Bjork, 2011;Peterson & Mulligan, 2013;Goossens et al, 2014;Abel & Bä uml, 2016), factual lists (Carpenter et al, 2008), face-name pairs (Carpenter & DeLosh, 2006), images (Pastötter et al, 2013), prose passages (Chan et al, 2006;Roediger & Karpicke, 2006b;Clark & Svinicki, 2014;Little & McDaniel, 2015;Bae et al, 2019), foreign language vocabulary (Kang & Pashler, 2014), brief multimedia lessons (Johnson & Mayer, 2009), PowerPoint presentations (Vojdanoska et al, 2009), and map-learning tasks (Carpenter & Pashler, 2007). However, no published studies have explored the testing effect on EFL students in particular.…”
Section: Introductionmentioning
confidence: 99%